MIGRATION OF AHISGA (MESKHETI) TURKS TO THE UNITED STATES AND LIVING THERE (Journal of history-rus, 2024)
The purpose of this study is to assess what Ahisga Turks have adopted in the process of immigrating to the United States and to discuss the methods individuals have developed to preserve their culture in the process of acculturation. Many factors influence this process at the same time. The Ahisga Turks, consisting of about 600 families from the Krasnodar region of Russia, settled in various states of the United States and later in the State of Ohio, forming the source of information. This study is based on data collected through in-depth interviews with ten people, nine Ahisga Turks and one cleric from Turkey, living in Dayton, Ohio, USA. The article contains both interviews and literature studies about Ahisga Turks living in the United States.The return of Ahisga Turks, who were exiled to Central Asia by the Soviet regime in 1944 for strategic reasons, is still being postponed for strategic reasons. In many countries, including Turkey, where Ahisga Turks live, international organizations and think tanks continue to solve the issue from a political and strategic point of view. As a concrete example, it can be shown that although the return of Ahisga Turks to their land is a condition for Georgia's membership in the Council of Europe (1999), neither the Georgian state nor the Council of Europe can implement the return process as intended.Keywords: Ahisga Turks, US Refugee Program, migration to the USA, ethnic cleansingin Russia, interviews in the USA, Ahisga Turkish American Community Center.